ANALYSIS OF THE SOCIAL NETWORKS’ IMPACT ON DEMOCRACY DEVELOPMENT - Andreeski, Cvetko; Blazhekovikj Toshevski, Marina; Odzaklieska, Dragica (Horizons - International Scientific Journal, 2021)
The Internet and social networks are of high importance in the modern world we live in. Whatever their perception is, whatever they are used for, they have a big influence over the people’s lives and they are main drivers for the changes that cause new challenges. The accessto the Internet and the contents placed on the network enable non-selective access to the contents in which the users are interested. The users can read arguments of opposing parties for the subjects they are interested in. So, in this study, we have analyzed the Internet users’ interest in using social networks in R. N. Macedonia, of the growth of the Internet users number, and the users’ interest in accessing the digital media sites. Based on such a cross-sectional analysis, and an analysis of the corresponding literature in this area, some concluding considerations on the democracy development in our country, have been brought.